Morphologic Spectrum of Undetermined Causes of Hemoptysis- A Pathologist's Role - Nidhya GANESAN; Umamaheswari GURUSAMY (Federation of Turkish Pathology Societies, 2020)
Objective: Hemoptysis is the expectoration of blood or blood-streaked sputum from the tracheobronchial tree. The etiology may derive from nonneoplastic conditions such as infections, chronic pulmonary diseases, and vasculitis or neoplastic causes. Sometimes a definitive cause for hemoptysis cannot be found after ample diagnostic workup. The role of biopsy in such cases is to help the clinician in arriving at the final diagnosis. Diffuse alveolar hemorrhage is the main histopathological finding in hemoptysis and it appears with diffuse chest infiltrates radiologically. Material and Method: A retrospective study of 2 years duration was conducted to identify the morphological spectrum of diseases presenting with hemoptysis. A total of 243 lung biopsies obtained by various methods were retrieved in this study period and 20 cases with hemoptysis of undetermined etiology were detected. Results: Based on imaging and histopathology findings, the etiological causes of hemoptysis were divided into hemoptysis with and without capillaritis or due to tumor/tumor-like lesions and due to miscellaneous conditions. The most common etiology was vasculitis followed by infections. Conclusion: Histopathology helps to detect the etiology, particularly in cases of hemoptysis due to non-immunologic causes. In immunologic cases, histopathological findings may support the diagnosis in correlation with the clinical/imaging features.